Spraying performance and deposition characteristics of an improved air-assisted nozzle with induction charging - Zhou, Huitao; Ou, Mingxiong; Dong, Xiang; Zhou, Wang; Dai, Shiqun; Jia, Weidong (Frontiers in Plant Science, 2024)
Electrostatic spraying technology can improve the efficiency of pesticide deposition on the surface of leaves and reduce the environmental pollution caused by pesticide drift, which has an important prospect in agricultural pesticide application. To improve the deposition and penetration of droplets in the crop canopy, we designed and optimized an air-assisted electrostatic nozzle and conducted the spraying performance experiment. Parameters such as charge to mass ratio, particle size were tested and analyzed to obtain the suitable operating parameters of nozzle. The results proved that the improved air-assisted electrostatic nozzle has good atomization and chargeability. There is a good charging effect with charging voltage of 3000 V~5000 V, the CMR increased 127.8% from 0.86 to 1.97 mC/kg as the charge voltage increases from 1000 V to 4000 V, at an air pressure of 1.0 bar and liquid flow rate of 200 ml/min. Furthermore, we designed a multi-factor orthogonal experiment which was conducted using a four-factor, three-level design to and investigate the effects of operational parameters and canopy characteristics analyzed the impact on droplet deposition and penetration under different operating parameters and canopy characteristics conditions. Analysis of variance (ANOVA) and F-test were performed on the experiment results. The results showed that: The factors effect on droplet penetration, in descending order, The significance of the effect of each factor on droplet penetration, in descending order, was as follows: spray distance, leaf area index, air pressure, air pressure × spray distance. The factors effect on The significance of the effect of each factor on abaxial leaf deposition, in descending order, was as follows: air pressure, spray distance, air pressure × charge voltage, spray distance × charge voltage and charge voltage. For optimal droplet penetration and abaxial leaf deposition, option A3 B1 D2 (air pressure 1.5 bar, spray distance 0.2 m, charge voltage 2500V) is recommend. The spray nozzle atomization performance and deposition regulation were studied by experimental methods to determine the optimal values of operating parameters to provide a reference for electrostatic spray system development.